1991
DOI: 10.1111/j.1476-5381.1991.tb12271.x
|View full text |Cite
|
Sign up to set email alerts
|

Inability of an opioid antagonist lacking negative intrinsic activity to induce opioid receptor up‐regulation in vivo

Abstract: It has recently been suggested that opioid antagonists may be divided into those possessing negative intrinsic activity (e.g. naloxone) and those with neutral intrinsic activity (e.g. MR2266). MR2266 was chronically administered to rats by subcutaneous infusion at a dose of 0.3 mg kg−1 h−1 for 1 week. This dose reduced ingestive behaviour and blocked the antinociceptive effects of a κ‐agonist, indicating occupation of opioid receptors in vivo. No supersensitivity could be detected to the antinociceptive action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…histamine H 2 receptors, β 2 -adrenoceptors, α 2 -adrenoceptors etc., whereas neutral antagonists do not (for review see Milligan and Bond 1997). Prolonged treatment of animals in vivo with the opioid inverse agonist naloxone up-regulates opioid receptors whereas the neutral antagonist MR2266 has no effect (Morris and Millan 1991). Most dopamine D 2 receptor antagonists with antipsychotic action up-regulate D 2 receptor density upon prolonged exposure and are inverse agonists (Wilson et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…histamine H 2 receptors, β 2 -adrenoceptors, α 2 -adrenoceptors etc., whereas neutral antagonists do not (for review see Milligan and Bond 1997). Prolonged treatment of animals in vivo with the opioid inverse agonist naloxone up-regulates opioid receptors whereas the neutral antagonist MR2266 has no effect (Morris and Millan 1991). Most dopamine D 2 receptor antagonists with antipsychotic action up-regulate D 2 receptor density upon prolonged exposure and are inverse agonists (Wilson et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, these antagonists can be considered as possessing negative agonist activity at 6 opiate receptors. The essential difference between 'pure' antagonists and those possessing 'negative agonist' properties was underlined in studies by Millan et al (1988) and Morris & Millan (1991), who showed that unlike naloxone long-term exposure to MR 2266 failed to up-regulate central I, 6 or K opiate binding sites or to produce supersensitivity to opiate agonists.…”
Section: Functional Dissociation Of Tolerance and Dependencementioning
confidence: 99%
“…As observed with opioid agonists, treatment with antagonists also affects the MOR-µ-MOR-µ* equilibrium. Generally, treatment with inverse agonists tends to sensitize MOR and enhance the active state (MOR-µ*) while neutral antagonists favor the MOR-µ ground state [45]. In addition, naloxone turns from a weak inverse agonist at DOR into a partial agonist at DOR upon pretreatment with an inverse agonist of DOR [46].…”
Section: Neutral Antagonists and Inverse Agonistsmentioning
confidence: 99%